Progressive cavitating leukoencephalopathy: Case report of a rare childhood onset neurodegenerative disease - Kekatpure, Minal V; Karthik, G A; Bhat, Venkatraman (Indian Journal of Child Health, 2014)
The leukoencephalopathies with cystic changes form a distinct subtype of childhood onset neurodegenerative disorders. This group has heterogeneous etiological differentials that primarily include mitochondrial disorders, some leukodystrophies and central nervous system infections. We report this case of a 17-month old girl who presented with seizures, episodic encephalopathy, elevated blood lactate level and lactate peak on magnetic resonance spectroscopy, a typical imaging picture noted on cranial magnetic resonance imaging and absence of deletions or duplications of mitochondrial deoxyribonucleic acid. Progressive cavitating leukoencephalopathy (PCL) is a recently described entity with only a few cases reported so far. We report the first case of PCL from India. Accurate diagnosis can be made, not only, by the presence of typical clinicoradiological findings of PCL, but also by the awareness of, and, ruling out of, the various other differential diagnoses that are discussed in detail below.